The information society in Algeria between the constraints of reality and future prospects: A field study of the reality of e marketing for university research production - benadjaimia, bouabdellah (Journal of Social Sciences and Humanities, 2024)
The information society in which information has become a symbol of development, control and influence. In this study, we made an attempt to lay the foundations of the information society, in Algeria, through the university institution, specifically the production of scientific information and its relationship to the movement of scientific research on the one hand, and its relationship to communication and information technologies on the other hand, To achieve the following objectives: linking the spaces, institutions and individuals involved in intellectual production in Algeria, and trying to adapt their behavior to approach and integrate into the information society, as well as achieving a distinguished information society at the level of the Algerian university sector as it is in all developed countries. The focus was on the following three indicators: Production of scientific information. Possession of communication technology, electronic dissemination of information, using information technologies, using the social survey method for a sample of university professors researchers, and we reached important results, most notably that the information society in Algeria still faces great objective difficulties at the level of will, means and even plans, in addition to the culture of paper bureaucracy that The administrative and institutional mentality is still imprinted in Algeria.